Pengaruh Budaya Organisasi, Kepuasan Kerja Terhadap Sikap Perubahan Organisasi Dengan Komitmen Organisasi Sebagai Mediasi - Rizky Hamid Nasution; Evi Susanti Tasri (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
The UPTD of the Protected Forest Management Unit (KPHL) of Pasaman Raya is one of the regional technical implementing units of the Forestry Service of West Sumatra Province. So that it becomes interesting to examine the attitude of organizational change in employees. This study aims to analyze organizational change that is influenced by organizational culture variables, job satisfaction and the mediating role of organizational commitment. The results of this study state that partially there is a significant influence between organizational culture and positive and insignificant effect on organizational change attitudes, organizational culture has a positive and significant effect on organizational commitment, work goals have a positive and insignificant effect on organizational change attitudes, work goals have a positive and significant effect on organizational change. positive and significant on organizational commitment, organizational commitment has a positive and significant effect on organizational change attitudes, organizational commitment becomes an intervention between organizational culture and organizational change attitudes and is not significant and organizational commitment becomes an intervention